2014
DOI: 10.1590/s0100-06832014000300032
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da intensidade de tráfego de tratores em alguns atributos físicos de um argissolo amarelo

Abstract: RESUMO O tráfego intenso das máquinas nos solos cultivados aplica diferentes tensões que combinadas com altos valores de umidade desses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
1
14
0
8
Order By: Relevance
“…Thus, studies have reported compaction problems in the topsoil under no-tillage (Bergamin et al, 2010;Valicheski et al, 2012;Valadão et al, 2015;Arcoverde et al, 2019a). The depth of the compacted layer depends on several factors, including machine traffic intensity (Becerra et al, 2010;Valadão et al, 2015;Trentin et al, 2018), soil texture and mineralogy (Bergamin et al, 2010), organic matter content (Mujdeci et al, 2017), soil water content (Kirnak et al, 2017;Trentin et al, 2018), mass of agricultural equipment (Cortez et al, 2014;Sivarajan et al, 2018), inflation pressure, tire type, and tractor mass distribution on the axles (Cunha et al, 2009;Becerra et al, 2010;Cortez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studies have reported compaction problems in the topsoil under no-tillage (Bergamin et al, 2010;Valicheski et al, 2012;Valadão et al, 2015;Arcoverde et al, 2019a). The depth of the compacted layer depends on several factors, including machine traffic intensity (Becerra et al, 2010;Valadão et al, 2015;Trentin et al, 2018), soil texture and mineralogy (Bergamin et al, 2010), organic matter content (Mujdeci et al, 2017), soil water content (Kirnak et al, 2017;Trentin et al, 2018), mass of agricultural equipment (Cortez et al, 2014;Sivarajan et al, 2018), inflation pressure, tire type, and tractor mass distribution on the axles (Cunha et al, 2009;Becerra et al, 2010;Cortez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The porosity values are suitable for sandy soils, since they are between 0.32 and 0.47 m 3 m -3 (Reichardt & Timm, 2004). Cortez et al (2014) found lower values of total soil porosity in the same Ultisol and verified a decrease in porosity when the machinery traffic increased.…”
Section: Resultsmentioning
confidence: 53%
“…Moreover, in the treatment with chisel, the soil resistance to penetration is smaller; being concluded in their study that the agricultural layer varies up to 0.30 m, depending on the tillage equipment. Cortez et al (2014) verified that the machinery traffic in sandy soil can affect the values of the attributes density and total soil porosity.…”
Section: Introductionmentioning
confidence: 85%
“…Logo, a resistência a penetração não prejudicou o desenvolvimento do sistema radicular da cultura da soja, por ser inferior ao limite de 2 MPa (SALES et al, 2016). Já Cortez et al (2014) constataram em seus estudos acréscimo nos valores de RP a partir da camada de 0,10-0,15 m de profundidade e atribuíram esse resultado às estruturas mais densas do solo oriundas do sistema convencional anterior que foram inadequadamente corrigidas para implantação do SPD.…”
Section: Resistência a Penetração (Rp)unclassified